Fifty Years of Taxation at the Federal Court of Appeal and the Federal Court - Provencher, Annick (The Federal Court of Appeal and the Federal Court: 50 Years of History, 2021)
The Federal Court of Appeal and Federal Court are unique among Canada's courts because they are itinerant – they hear cases in all parts of Canada – as well as being bilingual and bijural. This book was prepared for the celebration of the fiftieth anniversary of the Federal Courts in 2021. Seventy-eight current and retired judges and prothonotaries on the two courts were interviewed and are referred to throughout the book. The authors present a brief history of these courts and their predecessor – the Exchequer Court of Canada – and an overview of the courts' jurisdiction, decision-making trends, and unique attributes. There are chapters on each of the courts' specialties – administrative law, immigration and refugee law, intellectual property, security and intelligence, Indigenous issues, the environment, admiralty, labour and human rights, and tax. Chief Justice Noël and Chief Justice Crampton each contribute a chapter. The preface is by Justice Frank Iacobucci and the epilogue by Justice Robert Décary.